The first principle calculation of improving p-type characteristics of B x Al1-x N - Zhengqian Lu (Nature Portfolio, 2021)
Abstract AlN is one of the third-generation semiconductor materials with wide application prospects due to its 6.2 eV band gap. In the application of semiconductor deep ultraviolet lasers, progress is slow due to the difficulty in obtaining p-type AlN with good performance. In this paper, the commonly used way of Mg directly as AlN dopant is abandoned, the inhibition effect of the B component on self-compensation of AlN crystal was studied. The improvement of self-compensation performance of AlN crystal by B component is studied by first principles calculation. The results show that the addition of B component can increase the hole concentration of AlN, which is conducive to the formation of p-type AlN.